Scientific Landscape of Climate Change Impact on Child Health: A Bibliometric Analysis - Prasanna Kumar BM; Chandrika Doddihal; Tanuja Pattankar; Shailaja Patil (Medsci Publications, 2024)
Background: Understanding the relationship between climate change and child health is crucial for making informed decisions and implementing successful treatments. However, the extensive scientific literature on climate change and child health has not undergone a general dynamic quantitative examination. This bibliometric analysis was undertaken to study pertinent literature on climate change impact on child health over a 22-year period (2000-2022). Methods: change's A five-step PRISMA process was used to extract 1864 peer-reviewed journal articles from the Web of Science Core Collection database. The data was analysed using bibliometric software tools, including VOSviewer, CiteSpace, and Biblioshiny. Results: The annual publication patterns showed a steady increase in the number of articles published on climate change's impact on child health over the past 22 years. The most well-known climate change impact on child health monitoring articles was identified, as were the most active researchers and top-contributing nations in climate change impact on child health research. The most dependable information sources for academic researchers were further determined using the citation analysis of journals. Finally, science mapping analysis was used to visualize and study the conceptual and intellectual knowledge structures to chart the evolution of the research area related to climate change's impact on child health. Science mapping also identified emerging trends and intriguing research directions. Conclusions: This bibliometric analysis provides a comprehensive overview of the scientific landscape of climate change's impact on child health research. The findings highlight the growing interest in this field of research, as well as the key players and emerging trends. This study's results can inform future research priorities and develop effective interventions to protect children from the harmful effects of climate change.